2014
DOI: 10.1038/nrendo.2014.166
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the adrenocortical stem cell niche: implications for disease

Abstract: Stem cells are endowed with the potential for self-renewal and multipotency. Pluripotent embryonic stem cells have an early role in the formation of the three germ layers (ectoderm, mesoderm and endoderm), whereas adult tissue stem cells and progenitor cells are critical mediators of organ homeostasis. The adrenal cortex is an exceptionally dynamic endocrine organ that is homeostatically maintained by paracrine and endocrine signals throughout postnatal life. In the past decade, much has been learned about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 179 publications
(233 reference statements)
3
64
0
16
Order By: Relevance
“…The clinically approved drug [D-Trp6]LHRH thus might deliver the potential to improve steroidogenesis in transplanted adrenocortical cells. Such an artificial adrenal might also allow the in vitro study of adrenocortical stem and progenitor cells that, so far, were impossible to isolate and culture, probably due to the inability to reconstruct the 3D in vivo environment in a culture dish (25). Most importantly, the creation of an artificial adrenocortical tissue with long-term stability opens the possibility for the transplantation of these cells with the goal of treating patients with adrenocortical insufficiency or adrenal hyperplasia due to 21-hydroxylase deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The clinically approved drug [D-Trp6]LHRH thus might deliver the potential to improve steroidogenesis in transplanted adrenocortical cells. Such an artificial adrenal might also allow the in vitro study of adrenocortical stem and progenitor cells that, so far, were impossible to isolate and culture, probably due to the inability to reconstruct the 3D in vivo environment in a culture dish (25). Most importantly, the creation of an artificial adrenocortical tissue with long-term stability opens the possibility for the transplantation of these cells with the goal of treating patients with adrenocortical insufficiency or adrenal hyperplasia due to 21-hydroxylase deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In the zona glomerulosa, the outermost layer, undifferentiated cells are intermingled with the differentiated aldosterone-producing cells in both mice and humans (Heikkila et al, 2002;Nishimoto et al, 2010). The progenitors are displaced centripetally to maintain and adapt adrenocortical function, and finally they undergo apoptosis at the adrenocortical-medullary boundary (Walczak and Hammer, 2015). The regenerative capacity of the adrenal gland has been tested by adrenal enucleation studies, where medulla and most of the cortex was removed leaving behind just the adrenal capsule and the outermost layer of the cortex.…”
Section: Adrenocortical Stem Cellsmentioning
confidence: 99%
“…Several studies have provided evidence for the existence of adrenocortical cells with stem-like and progenitor-like capacities in various mammalian species like humans, mice, rats or even the common seal (for review see (Walczak and Hammer, 2015)). …”
Section: Adrenocortical Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicated that accelerated lineage tracing (marking cell renewal) after Prkar1a ablation was not accompanied by an increase in cell division but rather an acceleration of the centripetal differentiation process. The adrenal capsule and subcapsular/zG region harbor stem/progenitor cells, the progeny of which contribute to the homeostatic maintenance and renewal of the cortex (40). We used our microarray data to evaluate the role of constitutive PKA activation on progenitor compartment homeosta- 5 (insets, B).…”
Section: Pka-dependent Accelerated Cortex Renewal Is Counteracted By mentioning
confidence: 99%